Re-framing conceptual metaphor translation research in the age of neural machine translation: Investigating translators' added value with products and processes - Gary Massey (Peoples' Friendship University of Russia (RUDN University), 2021)
The exploratory study reported in this article is predicated on the notion that human translators' cognition represents a key added value over disembodied artificial intelligence. It re-frames the methods, data and results of a precursor study, and supplements them with additional data and analyses to develop a new cognitive perspective on re-positioning human translation competence and translators' expertise in the age of neural machine translation (NMT). The study is centred on an investigation of culturally specific complex conceptual metaphor in translation, and it melds a more conventional product-oriented approach with experimental translation process research (TPR). It indicates that human translators' decision-making and problem-solving at different levels of training and experience take place on a conceptual level. Compared with the translations of the same metaphors by publicly available NMT systems and by beginners as well as more advanced students, the product data of the professionals involved in the study produce more varied translation solutions, with a range of deviations from the standardised output. This suggests that, after accessing the conceptual level of meaning realised in a particular lexical form, experienced professionals, as a group, are able to generate multiple potential target-text solutions in order to reach their target audience. The supplementary process data indicates that they do so situationally, based on 4EA cognition, through intuition and/or deliberative rationality. It is this, the author argues, that is the distinguishing feature of seasoned professional translators and a hallmark of their added value.